2023
DOI: 10.1371/journal.pone.0287520
|View full text |Cite
|
Sign up to set email alerts
|

The sudden transition to online learning: Teachers’ experiences of teaching during the COVID-19 pandemic

Elham Goudarzi,
Shirin Hasanvand,
Shahin Raoufi
et al.

Abstract: Introduction The sudden transition from face-to-face teaching to virtual remote education and the need to implement it during COVID-19 initially posed specific challenges to educational institutions. Identifying and understanding teachers’ experiences pave the way for discovering and meeting educational needs. This study explored faculty members’ teaching experiences during the COVID-19 pandemic. Materials and methods The qualitative descriptive design via conventional content analysis was used. It was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…According to that study, teachers should become familiar with content development technologies. Therefore, the final result of their content production was non-standard [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…According to that study, teachers should become familiar with content development technologies. Therefore, the final result of their content production was non-standard [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that e-learning could be relished as a successful mode of medical teaching, and that it might be utilized as an alternative educational method [ 15 ]. Among the advantages of e-learning, one can mention the following:teaching regardless of time and place, cost-effectiveness, no need for physical presence, the existence of various choices, time-saving, and the development of cooperative learning types [ 16 ].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…During the pandemic, many faculty faced teaching-learning challenges as they moved forward, and it was well-known that effective planning was critical for switching to online teaching (Goudarzi et al, 2023). The study conducted by Perez-Echeverria et al (2022) showed that faculty aimed to select teaching practices that were more content-centered by using available online resources to better suit their teaching practices.…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%